Muros de cortante en estructuras de madera - Ordóñez Candelaria, V. Rubén (Instituto de Ecología, A.C., 1995)
Structural performance of shear walls was studied in this project, using the standard wall frame and  six different sheathings for structural uses in walls under racking loads. The sheathings tested were those deemed the most appropiate for the wood construction industry in Mexico. Curves of load deflection for racking test are presented to give an idea of the behavior of shear walls against racking loads (resulting from earthquake or wind). Also included are proposed design vales for each kind of sheathing and connector used.